Industry 4.0: Smart Contract-based Industrial Internet of Things Process Management - Garrocho, Charles Tim Batista; Ferreira, Célio Marcio Soares; Sacramento Júnior, Ailton Sávio; Cavalcanti, Carlos Frederico Marcelo da Cunha; Oliveira, Ricardo Augusto Rabelo (Anais Estendidos do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2019)
Through the Internet of Industrial Things, significant investments in the industry are expected. In this new environment, machine-to-machine communication showed immediate potential. However, most communication implementations require a trusted intermediary. The introduction of smart contracts can enable communication without the need for a trusted intermediary. To provide security and decentralization in industrial communication processes, smart contract-based middleware is proposed. This proposal is evaluated for impacts against the stringent communication requirements required by industrial applications. Experimental results show that while this approach offers greater security and decentralization than traditional proposals, blockchain-based smart contracts cannot yet be applied to industrial systems due to blocking time.